2015
DOI: 10.1111/1751-2980.12223
|View full text |Cite
|
Sign up to set email alerts
|

Liver cancer in Malaysia: Epidemiology and clinical presentation in a multiracial Asian population

Abstract: HCC is most common among Chinese, followed by Malays and Indians in Malaysia. The etiology of HCC shows a peculiar racial pattern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…The highest estimated difference in the rate of CRC was observed in Australia/New Zealand (44.8 and 32.2 per 100,000 in males and females, respectively), and a similar difference was observed in Western Africa (4.5 and 3.8 per 100,000 in males and females, respectively) [1]. In Malaysia, the same trend was observed in hepatocellular cancer, which is the second most common cancer after CRC in Malaysia and is 3.40 times likely to occur in males than females [5,13]. The reason why females exhibit a lower risk for CRC is unclear, but several studies have suggested that females hormones may have a protective effect against CRC by way of changes in bile synthesis and secretion that lead to a reduced concentration of bile acids in the colon [14,15].…”
Section: Discussionmentioning
confidence: 56%
“…The highest estimated difference in the rate of CRC was observed in Australia/New Zealand (44.8 and 32.2 per 100,000 in males and females, respectively), and a similar difference was observed in Western Africa (4.5 and 3.8 per 100,000 in males and females, respectively) [1]. In Malaysia, the same trend was observed in hepatocellular cancer, which is the second most common cancer after CRC in Malaysia and is 3.40 times likely to occur in males than females [5,13]. The reason why females exhibit a lower risk for CRC is unclear, but several studies have suggested that females hormones may have a protective effect against CRC by way of changes in bile synthesis and secretion that lead to a reduced concentration of bile acids in the colon [14,15].…”
Section: Discussionmentioning
confidence: 56%
“…Up to 30% of HCC can be attributable to cryptogenic cirrhosis; the majority of such cases are believed to be due to NASH . Cross‐sectional studies in Asian countries such as Malaysia, Japan, and Korea suggest that the contribution of NASH to HCC is lower than in the West and is in the region of 7–16% …”
Section: Epidemiologymentioning
confidence: 99%
“…Advanced stages are characterized by the presence of extra hepatic spread, vascular invasion, and the presence of cancer-related symptoms. 17 In this study, the majority of HCC patients were also positively infected with the hepatitis B virus. The hepatitis B is the most dominant risk factor for HCC cases.…”
Section: Discussionmentioning
confidence: 70%